Oxidation Behavior of Al-Y Coating on γ-TiAl at 900°C - Z G,Yang (2019)
ABSTRACT In this study, an Al-Y coating was applied to enhance the property of oxidation resistance on the surface of γ-TiAl alloys by rf magnetron sputtering. The isothermal oxidation tests were investigated at 900 °C for 100 h. The coating characteristics and microstructure of coating after isothermal oxidation were inspected by XRD and SEM methods respectively, and coating bonding strength was investigated by scratch tester. Results show that Al2O3 and Y2O3 were produced on the surface of γ-TiAl alloys to enhance oxidation resistance during the isothermal oxidation test. Diffusion layer with rich element of Al provides abundant Al to surface for formation of a continuous Al2O3 layer which increases oxidation resistance effectively. Oxides of YAlO3 and YAG were formed during the oxidation tests, which were beneficial for the strength, hardness and fracture toughness of crystal grain of Al2O3. Furthermore, Element of Ti diffused into surface from substrate was restrained by Al because of the formation of TiAl3 and TiAl, which avoid the layer-broken by titanium oxides with porous structure